Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

To solve the system of equations below, Grace isolated the variable [tex][tex]$y$[/tex][/tex] in the first equation and then substituted into the second equation. What was the resulting equation?

[tex]\[
\left\{
\begin{array}{l}
4 y = 8 x \\
\frac{x^2}{25} - \frac{y^2}{49} = 1
\end{array}
\right.
\][/tex]

A. [tex][tex]$\frac{x^2}{25} - \frac{4 y^2}{49} = 1$[/tex][/tex]

B. [tex][tex]$\frac{x^2}{25} - \frac{2 y^2}{49} = 1$[/tex][/tex]

C. [tex][tex]$\frac{x^2}{25} - \frac{4 x^2}{49} = 1$[/tex][/tex]

D. [tex][tex]$\frac{x^2}{25} - \frac{2 x^2}{49} = 1$[/tex][/tex]


Sagot :

To solve the system of equations:

[tex]\[ \left\{\begin{array}{l} 4 y = 8 x \\ \frac{x^2}{25} - \frac{y^2}{49} = 1 \end{array}\right. \][/tex]

we start by isolating the variable [tex]\( y \)[/tex] in the first equation.

First, solve for [tex]\( y \)[/tex] in the equation [tex]\( 4y = 8x \)[/tex]:

[tex]\[ 4y = 8x \][/tex]

Divide both sides by 4:

[tex]\[ y = \frac{8x}{4} \][/tex]

Simplify:

[tex]\[ y = 2x \][/tex]

Next, we substitute [tex]\( y \)[/tex] into the second equation ([tex]\( \frac{x^2}{25} - \frac{y^2}{49} = 1 \)[/tex]) in place of [tex]\( y \)[/tex]:

[tex]\[ \frac{x^2}{25} - \frac{(2x)^2}{49} = 1 \][/tex]

Simplify inside the parentheses:

[tex]\[ \frac{x^2}{25} - \frac{4x^2}{49} = 1 \][/tex]

Thus, the resulting equation is:

[tex]\[ \frac{x^2}{25} - \frac{4x^2}{49} = 1 \][/tex]

So, the correct answer is:

C. [tex]\(\frac{x^2}{25} - \frac{4x^2}{49} = 1\)[/tex]